Problematika Motivasi Belajar Siswa Kelas VIII dalam Pembelajaran Bahasa Arab SMP IT Yapidh - Hamdah, Laras (STAINI Press, 2022)
This study aims to find out the learning motivation of grade VIII students of SMPIT YAPIDH in the field of Arabic language studies and the efforts of teachers in fostering and improving the spirit and language skills. This research is a field study with a subject of grade VIII students numbering 30 people, data collection using observations and interviews. And data analysis using descriptive qualitative techniques. The results of the study intended that the motivation of students to learn Arabic at SMPIT Yapidh is divided into two, namely internal motivational problems and external motivational problems. Internal motivational problems include lack of vocabulary, difficulty to read Arabic writing, lazy feelings that arise from each student, and difficult to understand the rules of Arabic (science nahwu and shorof). While the problematika external motivation of students, among others, the creation of an Arabic language environment among students, not all teachers understand the intellectual differences between students, the forced entry of SMPIT Yapidh from parents not from themselves and differences in educational background between students. The efforts made by the teacher is to provide information about the urgency of learning Arabic and teaching with interesting methods such as game methods, and teachers keep the classroom atmosphere conducive.